2002
DOI: 10.1039/b109420n
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an equilibrium between selenides and osmium(viii) reagents and selenoxides and osmium(vi) reagents

Abstract: Driving the equilibrium between selenides and osmium(VIII) reagents with selenoxides and osmium(VI) by a subsequent reaction (rearrangement of allyl selenoxides to allyl alcohols or addition of osmium(VIII) species on C=C double bonds) to one side, allows the transformation of methyl geranyl selenides to linalool and of methyl citronellyl selenoxide to 6,7-dihydroxy citronellyl selenide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It was shown that both yield and enantioselectivity are influenced by the pH of the reaction medium. The procedure was also applied to practical syntheses of natural product derivatives [27]. This version of the AD reaction not only uses a more ecological co-oxidant, but also requires much less material: 87 mg of material (catalyst, ligand, base, reoxidant) is required to oxidize 1 mmol of the same alkene instead of 1400 mg when AD mix is used.…”
Section: Oxygen or Airmentioning
confidence: 99%
“…It was shown that both yield and enantioselectivity are influenced by the pH of the reaction medium. The procedure was also applied to practical syntheses of natural product derivatives [27]. This version of the AD reaction not only uses a more ecological co-oxidant, but also requires much less material: 87 mg of material (catalyst, ligand, base, reoxidant) is required to oxidize 1 mmol of the same alkene instead of 1400 mg when AD mix is used.…”
Section: Oxygen or Airmentioning
confidence: 99%